Pontefract: A Review of the Evidence for the Medieval Town. (1st August 2013) - Roberts, Ian; Whittick, Christopher
Abstract : The excavations carried out in the eastern part of Pontefract over the last quarter of a century have provided significant new information about the pre-Conquest settlement; the evidence providing a compelling case for Pontefract having been not only the site of the documented royal vill, but also that of an Anglo-Saxon minster. By comparison there is relatively little archaeological evidence for the twelfth-century borough and the later medieval town to the south-west of the castle, our understanding of which is still heavily reliant on documentary evidence.